Sleep Apnea: More than Just a Noise - Meenakshi, S; Raghunath, N (Journal of Orofacial Research, 1970)
Obstructive sleep apnea is a sleep disorder of airflow at the nose and mouth during sleep. Patients with undiagnosed sleep apnea represent a major public health problem. Dentalprofessionals have a unique doctor patient relationship that can help them in recognizing the sleep disorder and managing the patients along with a physician or a sleep specialist. Oral appliance therapy is an important treatment modality for sleep apnea patients. This article discusses the etiology, clinical features, diagnosis and various treatment options with special reference to oral appliances used for obstructive sleep apnea